Tingkat Kebugaran Jasmani dan Indeks Massa Tubuh Peserta Didik di SD Negeri Gejayan Kabupaten Sleman - Septyananda, Refri; Suripto, Agus Widodo (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the level of physical fitness and body mass index of students at SD Negeri Gejayan, Sleman Regency. The design of this study uses quantitative descriptive research with test and measurement survey methods. The method used in this study was a survey method using the TKJI and BMI test instruments consisting of a 40-meter short-distance run, a bending elbow hanging test, a sitting baring test, upright jumping, a 600-meter run, as well as height and weight measurements. Data analysis techniques using descriptive analysis of percentages using Microsoft Excel or SPSS. The results of the data analysis obtained the level of physical fitness of students in the "less once" category of 0 students (0%), the "less" category of 14 students (29%), the "moderate" category of 30 students (60%), the "good" category of 4 students (8%), and the "very good" category of 0 students (0%), while for BMI students were in the "very thin" category of 1 student (2%), the "moderate skinny" category was 14 students (29%), the "normal" category was 32 students (67%), the "moderately fat" category was 0 students (0%), and the "fat once" category was 1 student (2%).The conclusion obtained from this study is that most of the physical fitness levels of upper-class students of SD Negeri Gejayan, Sleman Regency, for the 2021/2022 school year are categorized as "good", while for the body mass index, it is categorized as "normal".